Stabilization of Coal Industry Depends on Improvement in the Railroad Situation - Howard N. Eavenson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
ALL of the matters so far taken up by the Institute Committee on Stabilization of the Coal Industry will be of help, but it seems to be that under present conditions not very much can be expected until the railroad situation has been improved. As an instance of this, I would cite the fact of our experience at our mines in West Virginia and Kentucky. During 1917 and 1918 at our West Virginia plants we produced for our own consumption, practically entirely in the Chicago district, about 4,750,000 net tons of coal. In 1919 our output was reduced to 3,500,000 tons, this being caused partly by the shortage of orders in the few months following the armistice, but more particularly by The car shortage which began last September and continued throughout the remainder of the year, with the exception of December. This car shortage has been more acute since the first of the year, and while we now have an actual capacity here of 20,000 tons daily and have the equipment to produce it, with the possible exception of a few houses, we are able to average only about 12,000 tons, and in consequence, about 30 per cent. of our by-product ovens in the Chicago district are idle, and a number of blast furnaces are down for the want of coke. These figures, of course, refer to conditions before the strike of switchmen in April was started.